Primary Immunodeficiency Disorders in India—A Situational Review - Jindal, Ankur Kumar; Pilania, Rakesh Kumar; Rawat, Amit; Singh, Surjit (Frontiers in Immunology, 2017)
Primary immunodeficiency disorders (PIDs) are a group of genetic defects characterized by abnormalities of one or more components of the immune system. Whilst there have been several advances in diagnosis, management and research in the field of PIDs, they continue to remain underdiagnosed, especially in the less affluent countries. Despite several limitations and challenges, India has advanced significantly in the field of PIDs in the last few years. In this review, we highlight the progress in the field of PIDs in India over the last 25 years, the difficulties faced by clinicians across the country, the current state of PIDs in India and the future prospects.